Faculty power and student integrity: student ratings of teaching in a community college - Hadden, Craig, author; Davies, Timothy Gray, advisor; Bowman, Linda S., committee member; Hall, Bruce, committee member; Banning, James H., committee member (Colorado State University. Libraries, 2004)
Despite numerous studies aimed at confirming the reliability, validity, and generalizability of student ratings of teaching, most of them concern the instrument itself. These studies are quantitative or meta-analyses rather than qualitative. The present grounded theory study concerns student candor and sincerity when completing these ratings. From the interviews with 12 students, the core category of power emerged. Through remarks instructors make about ratings as well as through their communication with students, their general attitude and personality traits, their treatment of students, and their pedagogical skills and practices, instructors have the power to create climates of fear or trust. Student candor and sincerity depend to a great extent on the level of fear or trust they feel, thus impacting the trustworthiness of instruments that may otherwise be reliable and valid.
Keywords: community colleges; community college education